2023
DOI: 10.21873/anticanres.16245
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Conjugated α-Bisabolol Suppresses FAK Phosphorylation and Induces Apoptosis in Pancreatic Cancer

Abstract: Background/Aim: α-Bisabolol is an essential oil component extracted from plants, such as chamomile. We have previously reported that α-bisabolol suppressed proliferation, invasion, and motility of pancreas cancer. Cyclodextrin improved the solubility of α-bisabolol, therefore it enabled to administer intravenously. The aim of this study was to clarify the effect of cyclodextrin conjugated αbisabolol (CD-BSB) and the signals pathways associated with α-bisabolol for pancreatic cancer. Materials and Methods: Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Kano et al [ 130 ] have recently synthesized cyclodextrin-conjugated α-bisabolol and tested it against pancreatic cancer cells. The authors reported significant modifications of cytomorphology, apoptosis induction, and the suppression of phosphorylation of focal adhesion kinase.…”
Section: Drug Delivery Systems Based On Chitosan/cyclodextrins For Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kano et al [ 130 ] have recently synthesized cyclodextrin-conjugated α-bisabolol and tested it against pancreatic cancer cells. The authors reported significant modifications of cytomorphology, apoptosis induction, and the suppression of phosphorylation of focal adhesion kinase.…”
Section: Drug Delivery Systems Based On Chitosan/cyclodextrins For Th...mentioning
confidence: 99%
“…One study also reports using an oral chitosan-based formulation that ensured desirable stability in a simulated gastrointestinal environment, with slow cumulative drug release displayed in simulated gastrointestinal fluids without enzymes and in body fluid [ 113 ]. As for pancreatic cancer, cyclodextrin-based formulations were reported for intravenous injection [ 128 , 130 ], oral delivery [ 133 ] (demonstrated by in vivo studies to facilitate absorption and avoid pre-systemic metabolism, increasing the bioavailability of the carried drug), and potential suitability for both oral and parenteral administration [ 131 ] (only tested in vitro). Differently, among the chitosan-based formulations designed for a specific type of administration for fighting pancreatic cancer, one was engineered for intravenous delivery via folate receptor targeting [ 135 ], and two were developed for oral administration based on the intrinsic properties of this natural polymer [ 136 , 138 ].…”
Section: Drug Delivery Systems Based On Chitosan/cyclodextrins For Th...mentioning
confidence: 99%